2001
DOI: 10.2166/wst.2001.0262
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of olive mill wastewater by the combination of Fenton's reagent and ozonation processes with an aerobic biological treatment

Abstract: Degradation of olive mill wastewater (OMW) by means of two chemical oxidation processes (Fenton's reagent and ozonation) and their consecutive treatments with aerobic microorganisms have been studied. Fenton's reagent treatment moderately reduces COD and to a greater extent the polyphenolic compounds. Ozonation contributed to low conversion of COD and moderate reduction of polyphenols. The aerobic biological treatments degrade to values higher than 70% and 90% for COD and polyphenolic compounds, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 5 publications
2
51
0
1
Order By: Relevance
“…These drawbacks may be overcome by using heterogeneous catalysts or by applying these treatments at neutral pH (Merayo et al 2016;Hermosilla et al 2012a). Beltrán-Heredia et al (2001) tested the use of sequential treatments with Fenton reagants and ozone.…”
Section: Fenton and Photo-fenton Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…These drawbacks may be overcome by using heterogeneous catalysts or by applying these treatments at neutral pH (Merayo et al 2016;Hermosilla et al 2012a). Beltrán-Heredia et al (2001) tested the use of sequential treatments with Fenton reagants and ozone.…”
Section: Fenton and Photo-fenton Processesmentioning
confidence: 99%
“…These drawbacks may be overcome by using heterogeneous catalysts or by applying these treatments at neutral pH (Merayo et al 2016;Hermosilla et al 2012a). Beltrán-Heredia et al (2001) tested the use of sequential treatments with Fenton reagants and ozone.Biodegradability improvement is generally difficult to demonstrate after the application of these highly oxidizing processes, since they are not selective and also remove biodegradable material. On the other hand, their use after a biological treatment, where almost all the biodegradable fraction has already been removed, has been reported REVIEW ARTICLE bioresources.com .…”
mentioning
confidence: 99%
“…Aktas et al have tested the lime treatment of OMW, achieving a low degree of removal (28%) of volatile phenols responsible for high COD values and moreover phytotoxic conditions. 10 Ozonation and the Fenton oxidation of OMW were investigated by BeltranHeredia et al 11 The results showed that Fenton treatment moderately reduced COD and to a greater extent the polyphenolic compounds, while ozonation contributed to low conversion of COD and moderate reduction of polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that the Fenton reagent could moderately reduce COD and to a greater extent the phenolic compounds (Beltran-Heredia et al 2001;Rivas et al 2001).…”
Section: Flocculation-clarificationmentioning
confidence: 99%